Significance of 1B and 2B domains in modulating elastic properties of lamin A - Bera, Manindra (Sci Rep, 2016)
Nuclear lamins are type V intermediate filament proteins which form an elastic meshwork underlying the inner nuclear membrane. Lamins directly contribute to maintain the nuclear shape and elasticity. More than 400 mutations have been reported in lamin A that are involved in diseases known as laminopathies. These mutations are scattered mainly in the lamin rod domain along with some in its C-terminal domain. The contribution of the rod domain towards the elasticity of lamin A molecule was hitherto unknown. Here, we have elucidated the significance of the 1B and 2B domains of the rod in modulating the elastic behavior of lamin A by single-molecule force spectroscopy. In addition, we have also studied the network forming capacity of these domains and their corresponding viscoelastic behavior. We have shown that the 1B domain has the ability to form a lamin-like network and resists larger deformation. However at the single-molecular level, both the domains have comparable mechanical properties. The self-assembly of the 1B domain contributes to the elasticity of the lamin A network.